PANDANGAN ISLAM TERHADAP MANAJEMEN RISIKO MELALUI TELADAN KISAH NABI YUSUF AS - Rohmaniyah, Rosy Tasliyatul; Cecep, Cecep (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
In carrying out the activities of daily life humans will always be faced with various possible risks either directly or indirectly. The risks that occur in life can be positive (beneficial risk) or negative (detrimental risk), hence humans are encouraged to plan carefully to minimize any possible negative risks that can harm themselves. In addition to minimizing the possibility of negative risks they also recommended to be able to overcome any negative risk with various actions called Risk Management.